Biomarkers and biometric measures of adherence to use of ARV‐based vaginal rings. Issue 1 (2nd May 2016) - Stalter, Randy M; Moench, Thomas R; MacQueen, Kathleen M; Tolley, Elizabeth E; Owen, Derek H; ,
Abstract : Introduction: Poor adherence to product use has been observed in recent trials of antiretroviral (ARV)‐based oral and vaginal gel HIV prevention products, resulting in an inability to determine product efficacy. The delivery of microbicides through vaginal rings is widely perceived as a way to achieve better adherence but vaginal rings do not eliminate the adherence challenges exhibited in clinical trials. Improved objective measures of adherence are needed as new ARV‐based vaginal ring products enter the clinical trial stage. Methods: To identify technologies that have potential future application for vaginal ring adherence measurement, a comprehensive literature search was conducted that covered a number of biomedical and public health databases, including PubMed, Embase, POPLINE and the Web of Science. Published patents and patent applications were also searched. Technical experts were also consulted to gather more information and help evaluate identified technologies. Approaches were evaluated as to feasibility of development and clinical trial implementation, cost and technical strength. Results: Numerous approaches were identified through our landscape analysis and classified as either point measures or cumulative measures of vaginal ring adherence. Point measurements are those that give a measure of adherence at a particular point in time. Cumulative measures attempt to measure ring adherence over a period of time. Discussion: Approaches that require modifications to an existing ring product are at a significant disadvantage, as this will likely introduce additional regulatory barriers to the development process and increase manufacturing costs. From the point of view of clinical trial implementation, desirable attributes would be high acceptance by trial participants, and little or no additional time or training requirements on the part of participants or clinic staff. We have identified four promising approaches as being high priority for further development based on the following measurements: intracellular drug levels, drug levels in hair, the accumulation of a vaginal analyte that diffuses into the ring, and the depletion of an intrinsic ring constituent. Conclusions: While some approaches show significant promise over others, it is recommended that a strategy of using complementary biometric and behavioural approaches be adopted to best understand participants' adherence to ARV‐based ring products in clinical trials.